(The Role of Biotechnology in the Food Industry) - Basrah Enie, A. (Warta Industri Hasil Pertanian, 1987)
Biotechnology are concern for some of the major changes in the development of food production and food processing industry. In this article the uses of biotechnology in agricultural raw material improvement, food ingredients and food additives production, and food processing are reviewed.